Solution blown nanofibrous air filters modified with glass microparticles - POLAT, YUSUF (SAGE PUBLICATIONS INC, 2021)
High-pressure drop and lower dust holding capacity reduce the performance of nanofibrous air filters. For that reason, this study was carried out to form filters with high-quality factor and high dust holding capacity, thanks to the glass particle additives. In this study, as an approach to such modifications, fluffy nanofiber webs were produced via solution blowing. Polyamide 6 (PA6) was chosen as the base for the nanofibrous mats, where glass microparticles were embedded as an additive to reduce web solidity. The effects of glass microparticle embedding on the filtration performance and pressure drop of the mats were investigated. SEM analysis was performed to analyze nanofiber diameter and morphology. Also, the barrier properties of samples were examined by air filtration and air permeability tests. Findings showed that the addition of glass particles did not alter fiber morphology significantly. However, lowering the pressure drop resulted in higher air permeability and better filtration performance in terms of the quality factor. Glass particles embedded composite samples exhibited a higher quality factor compared to the neat PA6 sample, and the PA6 + 5%GP sample has the highest quality factor value around 0.43. The filtration efficiency of this sample was 99.97% at an expense of 187.3 Pa pressure drop. The obtained enhancement was conducted to the lower solidity of composite webs which was 36% lower for the PA6 + 5%GP sample.
Keywords: Aerosol filtration; solution blowing; glass microparticles; nanofiber; FILTRATION; PERFORMANCE; REGIME